PORTABLE DESK DESIGN FOR STUDENTS IN NATURAL DISASTER EVACUATION FACILITIES - Kukuh Rizki Satriaji; Dwi Hatmojo Danurdoro; Kharista Astrini Sakya; Eljihadi Alfin (Ide dan Dialog Desain Indonesia (Idealog), 2020)
Education is one of the most important factors that will build the nation's character in the future. Even the goverment also explained that every citizen has the same right to obtain quality education, even though they are in remote, underdeveloped areas or those with special needs (Law No. 20 of 2003 article 5). One area that is deemed to have special needs is the post-disaster area.In the past few years,various regions in Indonesia have been affected by natural disasters, such earthquakes, floods, tsunamis, etc. For example is Lombok Island, which suffered a disaster due to the 2018 big earthquakes in Indonesia. The government, through the Ministry of Education and Culture, as well as several NGOs, has made several efforts by establishing emergency school tents at several refugee points, but usually not equipped with good facilities. Some emergency schools only consist of open tents, with students studying and writing on the floor. This research aims to make learning table design criteria for students in accordance with these conditions. The methods used in this research are site observation with open ended questions are given to students and teachers in emergency schools, then content analysis is conducted to determine the appropriate design criteria. The results of this study are expected to be implemented into a table design that is practical, lightweight, and easy to operate by considering its use by primary school students with emergency conditions.